HEALTHY SENIORS CLICC: FLEXIBILITY IS THE NAME OF THE GAME FOR OLDER ADULT VOLUNTEER "PEER" EDUCATION IMPLEMENTATION. (11th November 2018) - Jared, M; Cortes, T; Lucas, J; Lepore, D; Torres, A; Bello, J
Abstract: We created the Bronx Health Corps (BHC) to increase health literacy and provide self-management support for older adults in the Bronx. Our goal was to enroll 40 older adult volunteers and train them on disease management/health promotion. After completing the required education, the volunteers taught at partner Senior Centers. We faced unforeseen challenges in recruiting the peer educators. Through creative expansion of enrollment efforts, we compiled a dedicated intergenerational team of college social work interns, senior center program directors, individuals from health plans, civic organizations, and older adults from the community. In 12 months' time, the group educated 875 older adults (who signed into a total of 2226 classes). Participant satisfaction with the class was assessed with a 10-item Likert scale survey. Mean satisfaction rate was 9 (N=181). Six months after the education, 75% reported that the classes changed their health behavior; 79% reported that their health had improved (N=136).